2022
DOI: 10.3390/polym14204384
|View full text |Cite
|
Sign up to set email alerts
|

Fabric Insert Injection Molding for the Preparation of Ultra-High Molecular Weight Polyethylene/High-Density Polyethylene Two-Component Self-Reinforced Composites

Abstract: The fabric insert injection molding approach can be applied to produce easily recyclable self-reinforced polymer composites (SrCs) whose reinforcement and matrix are from the same polymer. However, the mechanical properties of the SrCs are usually limited due to the poor impregnation of the inserted fabric. In this work, the ultra-high molecular weight polyethylene (UHMWPE) fabrics were used as the insert, and the high-density polyethylene (HDPE) melt was injected to fill the mold cavity and impregnate the fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Behind other advantages (e.g., interfacial bonding, price, and lightness), the use of self-reinforced composites means that the old products from these composites can be re-processed without any necessary separation techniques. The latest trend in the field of self-reinforced composites is the idea of the over-molding of fibers or fabrics directly in the cavity of the injection mold [99][100][101][102]. For example, Andrzejewski et al [103] overmolded self-reinforced poly (ethylene terephthalate) (PET) sheets with the same matrix polymer.…”
Section: Mono-materials Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Behind other advantages (e.g., interfacial bonding, price, and lightness), the use of self-reinforced composites means that the old products from these composites can be re-processed without any necessary separation techniques. The latest trend in the field of self-reinforced composites is the idea of the over-molding of fibers or fabrics directly in the cavity of the injection mold [99][100][101][102]. For example, Andrzejewski et al [103] overmolded self-reinforced poly (ethylene terephthalate) (PET) sheets with the same matrix polymer.…”
Section: Mono-materials Approachmentioning
confidence: 99%
“…The achievements confirmed that the use of over-molding technology for the preparation of self-reinforced composites has the potential for commercial implementation, facilitating the recycling of materials. In other examples, Wang et al [101] used two layers of ultra-high molecular PE fabrics as inserts and high-density PE melt to fill the mold cavity and impregnate the fabrics, and Lee et al [102] proposed a 100% PP self-reinforced composite to produce a drone frame, where PP fiber was fabricated using spinning. Alternatively, Wis et al [105] prepared, also via over-molding, PLA onto PLA/jute-mat reinforced continuous fiber composite sheets.…”
Section: Mono-materials Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the principle of manufacturing by injection molding consists of heating and injecting the materials into a mold [91,92]. An advantage of injection molding over direct extrusion is that it results in materials with three-dimensional shapes for various industrial applications [110]. For instance, Jamadon et al carried out the synthesis of poly-lactic acid (PLA) reinforced with magnesium hydroxide (PLA/Mg(OH) 2 ) using the injection molding method to be applied in bone implants [111].…”
Section: Injection Moldingmentioning
confidence: 99%
“…The difference in melting temperatures determines the processing window, and various techniques have been developed to expand this temperature range for SPC production. These methods include hot compaction of fibers or tapes [2][3][4][5][6][7], film stacking [8][9][10][11], a combination of hot compaction and film stacking [12], co-extrusion [13][14][15][16], extrusion-calendering [17,18], insert injection molding [19][20][21][22][23], and 3D printing [24,25].…”
Section: Introductionmentioning
confidence: 99%